Segurança pública e participação social em Mato Grosso : as representações sociais de integrantes do conselho comunitário de segurança na região do Pedra 90 em Cuiabá - Lima, Gênison Brito Alves (2019)
The dissertation consists of a study regarding the "Public Security and social participation in Mato Grosso: social representations of members of the Community Council of security in the region of 90 Stone in Cuiabá", reflecting the reality of the Councils the community, while social participation mechanism, and your interaction with the other agencies of the criminal justice system in the realization of your wishes, as well as in the joints and assistance in State or municipal urbanization policies, sport, leisure, culture, combating truancy and conflict mediation. Its overall objective was to understand how the social representations of community safety advisers in the region of 90 Stone, about social control and public safety, interfered in the work of CONSEGs. For the theoretical basis if you have used the theory of social representations (TRS) by Serge Moscovici and his collaborators, adopting even principles of theory of communicative action of Jurgen Habermas. Research proposal had in principle adopted qualitative approach of outlining the case study, applied nature, and with regard to objectives-a descriptive study. The primary data were collected by means of the focal group technique and a closed questionnaire, while secondary collected through literature search and open sources, being all parsed content with support of QSR Nvivo, software. 12. At the end, the speeches and the seizure of social representations of Councillors, revealed the way in which diffuse relations between the community and the operators of the State are based, as a result of their practices as social control apparatus, and how they affect strongly the development of its activities in the area.